“Transcranial Doppler Evaluation Of Cerebral Hemodynamic Alteration In Preterm Neonates With Early Onset Sepsis - A One Year Hospital Based Observational Study At Kle Dr. Prabhakar Kore Hospital” - Patil, Ashwin; Chordiya, Paawan S.; Vipin, Raveena; Patil, Yash Ashwin (Journal of Neonatal Surgery, 2025)
Background: Early neonatal sepsis occurs within 3 days of birth, with 85% showing signs within 24 hours. It's linked to maternal bacteria transmission, primarily cervicovaginal. This study assesses transcranial Doppler ultrasound for measuring cerebral blood flow as a diagnostic marker for early-onset neonatal sepsis in preterm infants with risk factors. Aim: To assess cerebral blood flow changes using transcranial Doppler ultrasound in preterm neonates with early onset sepsis. Methods: This Observational study conducted at ‘KLE's Dr. Prabhakar Kore Hospital & MRC, Belagavi’, from January 1 to December 31, 2021 included 60 preterm neonates (<37 weeks gestation) - 30 with EONS and 30 controls. Transcranial Doppler ultrasound was used to measure ‘resistivity index’ and ‘pulsatility index’ in the ‘middle cerebral artery’ and ‘anterior cerebral artery’ within 72 hours of birth. Results: Neonates with EONS had significantly lower mean RI and PI values in both MCA and ACA compared to controls (p<0.001). Median MCA-PI was 0.76 in EONS group vs 1.43 in controls. Median MCA-RI was 0.33 in EONS group vs 0.74 in controls. Similar reductions were seen in ACA indices. Vaginal delivery, prolonged rupture of membranes, and meconium-stained liquor were common risk factors in the EONS group. Conclusion: Preterm neonates with EONS demonstrate increased CBF as evidenced by lower RI and PI values on transcranial Doppler. Risk factors include vaginal delivery, PMRM, meconium-stained liquor, and prolonged labor. This non-invasive technique may be useful for early detection of EONS in preterm infants.